2022
DOI: 10.3389/fimmu.2022.1068260
|View full text |Cite
|
Sign up to set email alerts
|

JAK–STAT signaling pathway in the pathogenesis of atopic dermatitis: An updated review

Abstract: Atopic dermatitis (AD) is a chronic, inflammatory, pruritic form of dermatosis with heterogeneous manifestations that can substantially affect patients' quality of life. AD has a complex pathogenesis, making treatment challenging for dermatologists. The Janus kinase (JAK)–signal transducer and activator of transcription (STAT) pathway plays a central role in modulating multiple immune axes involved in the immunopathogenesis of AD. In particular, Th2 cytokines, including interleukin (IL)-4, IL-5, IL-13, IL-31, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 136 publications
2
57
0
Order By: Relevance
“…The different pharmacodynamic properties of JAK inhibitors and especially different selectivity for JAK isoforms may explain these findings. 17 For instance, baricitinib inhibits both JAK1 and JAK2 tyrosine kinases, while abrocitinib and upadacitinib are more selective for JAK1. [18][19][20] Different affinity for JAK1 and concomitant inhibitory activity on JAK2 and JAK3 pathways may explain why abrocitinib was effective in a subset of patients previously treated with other JAKi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different pharmacodynamic properties of JAK inhibitors and especially different selectivity for JAK isoforms may explain these findings. 17 For instance, baricitinib inhibits both JAK1 and JAK2 tyrosine kinases, while abrocitinib and upadacitinib are more selective for JAK1. [18][19][20] Different affinity for JAK1 and concomitant inhibitory activity on JAK2 and JAK3 pathways may explain why abrocitinib was effective in a subset of patients previously treated with other JAKi.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, eight of these patients (8/14) showed good clinical response to abrocitinib treatment. The different pharmacodynamic properties of JAK inhibitors and especially different selectivity for JAK isoforms may explain these findings 17 . For instance, baricitinib inhibits both JAK1 and JAK2 tyrosine kinases, while abrocitinib and upadacitinib are more selective for JAK1 18–20 .…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, AD lesional skin shows hyperkeratosis, acanthosis, and spongiosis [ 36 ]. Studies have suggested that activating the JAK/STAT signaling pathway and producing Th2 cytokines may also contribute to developing spongiosis in AD [ 22 , 24 , 36 ]. This was also confirmed in our research results ( Figure 1 and Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…They can lead to the recruitment of immune cells to the site of inflammation and exacerbation of AD symptoms. Th2 cytokines also contribute to skin barrier dysfunction by activating the Janus kinase-signal transducer and activator of transcription (JAK/STAT) pathway and reducing the production of skin barrier proteins [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the FDA added a boxed warning for JAK inhibitors, including baricitinib, abrocitinib and upadacitinib, for the treatment of arthritis and other inflammatory diseases as well as atopic dermatitis to include information about risk of major adverse cardiac events (MACEs), venous thromboembolic events (VTEs) and cancers 7,8 . Recently, several meta‐analyses on the safety of JAK inhibitors have been published 9–12 .…”
Section: Introductionmentioning
confidence: 99%